Evaluation of IPM modules for the management of Leucinodes orbonalis in brinjal - Nayak, U S; Rath, L K; Baral, K (Indian Journal of Plant Protection, 2020)
Field experiments were carried out to evaluate the performance of some IPM modules against Leucinodes orbonalis Guene on brinjal at Keonjhar district of Odisha during Kharif 2009 and 2010. The findings of the two years experiments revealed that the IPM module comprising of soil application of cartap hydrochloride 4 G @ 1 kg a.i./ ha at 2 weeks of transplanting, intercropping with coriander in 3:1 ratio, alternate foliar spray of indoxacarb 14.5 SC @ 1 ml/l of water and rynaxypyr 20 SC @ 0.35 ml//l of water at 10 days interval twice at vegetative stage and six times commencing from fruiting stage and regular collection and destruction of infested shoots and fruits was found to be highly effective in minimizing the infestation of L. orbonalis with 84.11, 77.06, and 77.44 per cent reduction in shoot, flower bud and fruit damage respectively, over the farmers’ practice of indiscriminate application of different insecticides. This module resulted in the highest marketable fruit yield (231.02 q/ha) and maximum net return of Rs. 1,09,878.00 per hectare.